An experimental investigation on the FPZ properties in concrete using digital image correlation technique - Wu, ZhiMin; Rong, Hua; Zheng, JianJun; Xu, Feng; Dong, Wei (Engineering fracture mechanics, 2011)
► The DIC method is used to investigate the FPZ properties in concrete. ► The FPZ length initially increases and then decreases with the crack propagation. ► The FPZ length at peak load increases with an increase in ligament length. ► The crack extension length at the peak load is about 0.25 times the ligament length. This paper presents an experimental investigation on the properties of the fracture process zone (FPZ) in concrete using the digital image correlation (DIC) technique. Based on the experimental results, it is found that the FPZ length increases during crack propagation but decreases after the FPZ is fully developed. The FPZ length at the peak load and the maximum FPZ length increase with an increase in specimen height, but decrease by increasing the notch depth to specimen height ratio. It is also found that the crack extension length at the peak load is about 0.25 times the ligament length.